Full Issue Vol 1 (2023) (Universitas Terbuka, 2023)
DEAN OF FACULTY OF LAW, SOCIAL AND POLITICAL SCIENCES REMARKS The 5th Open Society Conference “EMPOWERING TECHNOLOGY: HUMANITIES, BUSINESS & POLITICAL PERSPECTIVES IN VUCA ERA” OSC Welcome Speech Excellency Dr. H. Emil Elestianto Dardak, B.Bus., M.Sc. – Vice Governer of East Java, Indonesia. Excellency Steve Nouri – Chief AI Evangelist. Excellency Carin Holroyd, Ph.D. – Associate Professor in Political Studies and the Chair of the International Studies Program at the University of Saskatchewan. Excellency Rahmat Budiman, M.Hum., Ph.D. – Vice Rector of Institutional Development and Partnership at Universitas Terbuka, Indonesia. And Secretary General of AAOU. Excellency Ismail Fahmi – Founder at Media Kernels Indonesia. Excellency Assoc Prof Dr Ahmad Izanee Awang - President of OUM Excellency Dean of Faculty of Social and Political Sciences of University of Jember, Dr. Djoko Poernomo, M.Si., CIQnR. Excellency Dean of Faculty of Social and Political Sciences of Padjajaran University, Dr. R. Widya Setiabudi Sumadinata Excellency Prof.Ojat Darojat, M.Bus, PhD, Rector of Universitas Terbuka Honorable Vice Rectors, Dr. Mohamad Yunus, S.S., M.A. - Vice-Rector for Academic Affairs - Prof. Dr. Ali Muktiyanto, S.E., M.Si. - Vice-Rector for Finance, Resource, and General Affairs - Dr. Paken Pandiangan, S.Si., M.Si. - Vice-Rector for Information System and Students Affairs And all participants of the seminar, Bismillahirrohmanirrohim. Assalammualaikum, wr.wb. Good morning and a very welcome to the 5th Open Society Conference 2023 – a convergence of brilliant minds, visionary thinkers, and dynamic change-makers! We are delighted to have you all gathered here today as we embark on a journey to explore the theme that lies at the heart of our times: “Empowering Technology: Humanities, Business, and Political Perspectives in the VUCA era. In this era of rapid change and uncertainty, our world has become increasingly Volatile, Uncertain, Complex, and Ambiguous (VUCA). Technological advancements have reshaped the way we live, work, and interact, bridging gaps across industries, nations, and cultures. The interplay between technology, humanity, and politics has become a driving force that shapes the trajectory of our future. Today, this conference will serve as a crucible of ideas, a platform for deep exploration, and a space for collaboration that transcends disciplines and boundaries. We have gathered some of the brightest minds from around the globe – from the fields of humanities, business, and politics – to share their insights, experiences, and strategies on how to harness the power of technology to not only navigate the VUCA landscape but also thrive within it. As we stand at this juncture of knowledge and possibility, let us remember that the potential of technology is immense, but so too are the responsibilities it places upon us. As we ponder the digital transformations that are sweeping across our societies, let us also reflect on the enduring values of empathy, equity, and ethics. It is at the intersection of technology and humanity that we must forge a path toward a future that is not only advanced but also just inclusive and sustainable. I encourage you all to actively participate, engage in vibrant discussions, share your insights, and foster connections that transcend the confines of this conference. Let us learn from one another, challenge our assumptions, and envision a world where technology is a force for empowerment, progress, and positive change. In conclusion, the 5th Open Society Conference 2023 is not just a gathering of brilliant minds; it is a convergence of thought leaders who understand that our shared future is intricately woven with technology’s rapid advancement. Let us embark on this journey of exploration, learning, and collaboration with open minds and hearts, embracing the challenges and opportunities of the VUCA era. Thank you and let the conference begin! Wassalammualaikum, wr.wb. Signed Muhammad Husni Arifin, S.Ag., M.Si., Ph.D. Dean of Faculty of Law, Social and Political Sciences